ENVIRONMENTAL RESPONSE AND pH TOLERANCE OF INDUCED CO2 IN ULVA RIGIDA C. AGARDH, 1823 (CHLOROPHYTA) UNDER CONTROLLED CONDITIONS - A. O. Amosu; D. V. Robertson-Andersson; G. W. Maneveldt; J. L. Knapp; L. Auersward; J. J. Bolton (Journal of Animal and Plant Sciences, 2022)
The increase in integrated multitrophic aquaculture (IMTA), where seaweed (particularly Ulva rigida C. Agardh, 1823) is used as a feedstock and a wastewater scrubber in South African IMTA systems, has necessitated research into seaweed growth rates, which has subsequently increased production technologies. Seaweed growth can be increased by controlling the culture media. One of the means to control growth rate is through CO2 gas addition to culture media via aeration. This has the potential added benefit of using waste CO2 production from an alternative source to decrease overall carbon dioxide emissions. The consequence of elevated CO2 concentration on the pH of culture medium and the equivalent functional reactions in the seaweed were examined using U. rigida in flow-through systems. Toxicity investigation of Hydrogen ion concentrations were carried out on U. rigida to examine their anatomy cum functional differences arising due to CO2 exerted stress. Elevated CO2 levels and the accompanying decrease in culture media pH (4.71 – 6.67) lead to a significant decrease in biomass with varied sporulation activities. In addition, U. rigida in flow-through systems showed a gradual degeneration in specific growth rate, from day 7, at varying rates until the end of the experiment in the following sequence pH 7.20 > 8.20 > 7.50 > 7.80. The treatment set at pH 7.20 yielded the greatest specific biomass and the greatest produce. The cultured input stocking rate of 5 g.l-1 of seawater proved to be suitable for cultivation. The pH toxicity reaction was significant in predicting the suitability of seaweed cultured under CO2 induced concentrations.
Keywords: Increased CO2 concentrations; Ocean acidification; pH; physiochemical characteristics; seaweed; sequestration; Ulva rigida